1990
DOI: 10.1182/blood.v76.12.2462.2462
|View full text |Cite
|
Sign up to set email alerts
|

Donor leukocyte transfusions for treatment of recurrent chronic myelogenous leukemia in marrow transplant patients

Abstract: Three patients with hematologic relapse after bone marrow transplantation for chronic myelogenous leukemia were treated with interferon alpha and transfusion of viable donor buffy coat. All had complete hematologic and cytogenetic remission, which persisted 32 to 91 weeks after treatment. In two patients graft-versus-host disease developed and was treated by immunosuppression. These results are an example of adoptive immunotherapy without cytoreductive chemotherapy or radiotherapy in human chimeras.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
294
1
6

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,387 publications
(306 citation statements)
references
References 20 publications
5
294
1
6
Order By: Relevance
“…Especially in patients with a relapse from CML after BMT, treatment with infusion of lymphocytes from the original marrow donor may induce second complete remission (Cullis et al, 1992;Drobyski et al, 1992;Kolb et al, 1990Kolb et al, , 1995. 11 patients who relapsed from CML-CP1 were treated with lymphocyte infusions from the donor and nine patients (82%) responded.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in patients with a relapse from CML after BMT, treatment with infusion of lymphocytes from the original marrow donor may induce second complete remission (Cullis et al, 1992;Drobyski et al, 1992;Kolb et al, 1990Kolb et al, , 1995. 11 patients who relapsed from CML-CP1 were treated with lymphocyte infusions from the donor and nine patients (82%) responded.…”
Section: Discussionmentioning
confidence: 99%
“…Problems associated with DLI, including GVHD or delayed response (usually 4 weeks), prompted mHag researchers to test the effects of adoptive immunotherapy with mHag-specific CTL clones against recurrent leukemia. (3) A protocol to generate HA-1 H and HA-2 V specific T-cell lines from mHag-negative donors was proposed for adoptive immunotherapy. (15) Another adoptive immunotherapy trial using CTL clones that lyse hematopoietic cells but not dermal fibroblasts has been performed in the Fred Hutchinson Cancer Research Center, (50) where a dramatic decline of cytomegalovirus (CMV)-related disease has already been demonstrated by adoptive transfer of CMV-specific CTL clones.…”
Section: Clinical Application Of Mhagmentioning
confidence: 99%
“…Recently, it has been shown that the administration of donor leucocytes given at the time of leukaemic relapse after allogeneic BMT can produce haematological and cytogenetic remissions ( Jiang et al, 1993;Kolb et al, 1990;Porter et al, 1994;Szer et al, 1993). However, the high incidence of severe GVHD and prolonged periods of pancytopenia induced by the infusion of immunocompetent T lymphocytes represent major obstacles to the success of this therapy.…”
Section: Gvhdmentioning
confidence: 99%